Patientnärmre vård: En observationsstudie av sjuksköterskans tid för patientnära vård. (December 2014) - Magnusson, Carl; Ekebergh, Margaretha; Jutengren, Göran; Knutsson, Susanne
The aim: To conduct a follow up study to measure registered nurses' time of direct patientcare after implementation of patientfocused care (PFC). Background: PFC is an organizational model with the objective to increase both patient participation and health care effectiveness. After a reconstruction of wards to single bedrooms in a hospital south of Sweden. PFC was implemented to increase time for direct patientcare in order to better meet patients' needs. Method: Time measured observations were conducted. 20 registered nurses were observed in four different wards at a 525-bed hospital in south of Sweden after implementation of PFC. Findings: In a workday of 8, 5 hrs, registered nurses spend 6, 8 hrs (79, 8%) with work related to patients. Time for directcare was 2 hrs (23, 8%) and time for indirect care was 4, 8 hrs (56%). Indirect care consists of categories such as documentation, report and medical round. Conclusion: In comparison before implementation of PFC, time for patientrelated care increased by 10, 8%. However, time is spent mainly at patient indirectcare activities. It is important to also focus on a change of culture in the organization to succeed with an implementation of PFC.